How do Travel Bloggers Influence Generation Z‘s Travel Decisions? An Exploratory Study through Five Italian Famous Travel Bloggers - Elisa Rancati; Alessandro d’Agata (European Scientific Journal, ESJ, 2025)
The increasing adoption of new communication channels such as social networks among Generation Z has created new professional job roles over the last decade, including travel bloggers. This paper focuses on understanding the influence of travel bloggers on Generation Z’s travel decisions. A mixed qualitative and quantitative survey design was employed for this study. Empirical data were drawn from 475 Generation Z travelers in Italy using a purposive sampling technique. The quantitative component involved a structured questionnaire consisting of four sections and thirty questions, including demographic information, travel habits, and perceptions of travel bloggers’ influence. Responses were collected via face-to-face interviews and analyzed using SPSS (Statistical Product and Service Solutions). Data analysis included descriptive statistics, t-tests to compare sample means, and Likert-scale evaluations to measure the frequency of social media usage in travel decision-making. Findings reveal that travel bloggers play a moderately relevant role in Generation Z’s travel decisions, particularly in the realm of social and mobile business. This study contributes to the literature in several ways. First, it enriches Generation Z travel decision-making theory by providing empirical evidence on factors leading to increased influence sharing among travelers. Second, it expands knowledge on the role of influencers, particularly regarding video and photo content in online tourism communities. From a managerial perspective, the study highlights key drivers of travel decision-making in Generation Z within social networks, and it provides strategic guidelines for travel bloggers to effectively promote tourism destinations. To the best of the authors’ knowledge, this study is among the first to empirically investigate the impact of travel bloggers on the tourism decision-making process of Generation Z travelers in the hospitality and tourism literature.